Autopsi Medis dalam Hukum Islam: Keseimbangan antara Ilmu Pengetahuan dan Kehormatan Jenazah - Rania Shaima Farha; Callista Yumna; Fatimah Azzahra (Pusat Riset dan Inovasi Nasional, 2024)
Medical autopsy is a procedure aimed at conducting a thorough examination of the deceased to identify the cause of death and analyze underlying health conditions. This practice plays a crucial role in the medical and forensic fields, where autopsy results can provide vital information for legal purposes, death investigations, and the advancement of knowledge in health. In Islamic law, medical autopsy is a procedure performed to determine the cause of death and understand the health condition of the deceased individual. This study aims to explore the balance between scientific knowledge and respect for the deceased in autopsy practices, focusing on the Islamic legal perspectives that regulate its implementation. The research method employed is qualitative, relying on the analysis of relevant scientific articles and journals, covering five main aspects related to medical autopsy, Islamic law views, and the fatwas of scholars regarding its implementation. The findings indicate that autopsy, while important for medical and legal purposes, must be conducted with consideration for the principle of respect for the deceased and is only permissible under certain conditions that do not violate the dignity of the body. The implications of this study highlight the need for the integration of science and ethics in the execution of medical autopsies, as well as the importance of disseminating clear fatwas to guide the community and authorities.